2002
DOI: 10.1038/sj....bjc.6600185...
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the oxaliplatin-5 fluorouracil-folinic acid combination on respective intracellular determinants of drug activity

Abstract: The combination of 5-fluorouracil-folinic acid and oxaliplatin has led to a significant improvement of chemotherapy efficacy in advanced pretreated colorectal cancer. The objective of the present study was, considering the oxaplatin-5-fluorouracil-folinic acid combination, to examine the impact of one given drug on the cellular determinants of cytotoxic activity of the other drug. These cellular factors were analysed on the human colon cancer cell line WiDr in clinically relevant conditions of drug exposure ('… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Experiments looking at the mechanism of synergism between oxaliplatin and 5-fluorouracil (5fu) have uncovered a direct inhibitory effect of oxaliplatin on thymidylate synthase, preventing the incorporation of thymidine in nucleic acid synthesis 9 . This antimetabolite-like effect results in arrest of the mitotic process.…”
Section: Arrest Of Dna Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments looking at the mechanism of synergism between oxaliplatin and 5-fluorouracil (5fu) have uncovered a direct inhibitory effect of oxaliplatin on thymidylate synthase, preventing the incorporation of thymidine in nucleic acid synthesis 9 . This antimetabolite-like effect results in arrest of the mitotic process.…”
Section: Arrest Of Dna Synthesismentioning
confidence: 99%
“…The exact mechanism of synergism between 5fu and oxaliplatin is complex, but experimental observations suggest that oxaliplatin can downregulate or inhibit dihydropyrimidine dehydrogenase, slowing the catabolism of 5fu 9 .…”
Section: Mechanism Of Action In Oxaliplatin-based Combinationsmentioning
confidence: 99%
“…[50][51][52][53][54] The efficacy of oxaliplatin plus LF (Oxali-FUFA) as first line of chemotherapy has been largely demonstrated in the last years in a large number of different clinical trials performed in patients with metastatic colo-rectal carcinoma. 51,55 More recently, it has been shown that Oxali-FUFA (following the FOLFOX 4 schedule proposed by De Gramon) is better tolerated, and leads to a higher objective response rate, a longer time to progression, and a longer overall survival than the IRI, LF, and 5-FU combination (ILF) proposed by Salts et al in patients with advanced colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of synergism of combinational treatment of OXA and 5-FU is complex, but experimental observations suggest that OXA can downregulate or inhibit dihydropyrimidine dehydrogenase, slowing the catabolism of 5-FU. [57][58][59] In our study, the in vitro cytotoxic effect of combining OXA (39 µM) and 5-FU (120 µM) was 1.65 and 1.44 times higher than that of the same amounts of OXA and 5-FU alone, respectively. Moreover, the cytotoxicity of a combination of free OXA (39 µM) and 5-FU (120 µM) was 1.80 times enhanced by treatment with a nanoemulsive form containing OXA/DCK (39 µM) and 5-FU (120 µM).…”
mentioning
confidence: 49%